Comparative transcriptome analysis of bovine blastocysts reveals specific effects of the oocyte source and the environments during maturation and early embryo development - Mohammad Bozlur Rahman; Eva Held-Hoelker; Mohammed Saeed-Zidane; Franca Rings; Dessie Salilew-Wondim; Dawit Tesfaye; Ahmed Gad; Samuel Gebremedhn; Ernst Tholen; Karl Schellander; Christine Große-Brinkhaus; Michael Hoelker (BMC Genomics)
Abstract Background Although differences between in vivo and in vitro derived bovine blastocysts in terms of global gene expression profiles have been reported, comparative transcriptome analyses specifically addressing the sustained impact of the oocyte source or the in vitro culture environments during maturation and post-maturation period are remain limited. Therefore, the present study aimed to investigate the specific impacts of oocyte origin and the culture environment during and after maturation on the gene expression signature at blastocyst stage. To achieve this, we utilized our recently developed technique that enables intrafollicular transfer of immature and matured slaughterhouse-derived oocytes into dominant or preovulatory follicles. Results The presents study identified a total of 1052 differentially expressed genes between in vitro and in vivo derived blastocysts, many of which are involved in key pathways related to protein synthesis, protein degradation and cell-cycle regulation. The majority of these genes (n = 913), particularly those associated with “ubiquitin mediated proteolysis”, “proteasome activity” as well as “cell cycle” related pathways, were differentially expressed due to the in vitro environment following oocyte maturation. Moreover, a distinct set of genes (n = 109) including DHCR7, DHCR24, HMGCR, HMGCS1 and SCD5, which are crucial for cholesterol biosynthesis and lipid metabolism, were altered in response to the in vitro environment during oocyte maturation. Notably, the origin of the immature oocyte also appeared to predetermine the later expression outline of a set of genes (n = 28), including DLD and PLAC8, which are implicated in implantation success and calf delivery. Conclusions The present study provides a comprehensive overview of transcriptomic alterations and pathway disruptions resulting from the in vitro environment following oocyte maturation, offering insight into potential mechanisms underlying embryonic genome activation, DNA duplication and appropriate cell cleavage. The differential expression of genes involved in cholesterol biosynthesis and lipid metabolism due to the in vitro maturation environment may contribute to the reduced cryotolerance observed in the resulting blastocysts. Furthermore, dysregulation of specific genes as a consequence of oocyte source has implications for post-implantation developmental competence. Collectively, these findings advance our understanding of the molecular determinants affecting embryonic developmental potential. The expression signature of these pathways could therefore be used to assess the impact of various treatments and culture environments on embryonic development. In addition, the insights gained from this study could inform future strategies to improve the quality of embryos in in vitro production systems through the targeted modulation, either enhancement or inhibition, of specific genes or pathways.